2009
DOI: 10.3346/jkms.2009.24.6.1015
|View full text |Cite
|
Sign up to set email alerts
|

Differential Immunohistological Features of Inflammatory Myopathies and Dysferlinopathy

Abstract: This study was performed in order to characterize the types of the infiltrating cells, and the expression profiles of major histocompatibility complex (MHC) class I and membrane attack complex (MAC) in patients with inflammatory myopathies and dysferlinopathy. Immunohistochemical stains were performed using monoclonal antibodies against several inflammatory cell types, MHC class I, and MAC in muscles from inflammatory myopathies and dysferlinopathy. There was significant difference in the types of infiltrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 25 publications
0
38
0
1
Order By: Relevance
“…The first symptom presented was repeated pitting edema and numbness in the lower limbs, unlike most of the reported dysferlinopathies. 13,14 In the second biopsy of this patient, we also see a large number of lymphocyte infiltrations around small blood vessel of the perimysium besides a severe variation of fiber size with a lot of degenerating, necrotic, and regenerating fibers. Patients with muscular dystrophy often have slight numbness, which can have spontaneous resolution.…”
Section: Discussionmentioning
confidence: 72%
“…The first symptom presented was repeated pitting edema and numbness in the lower limbs, unlike most of the reported dysferlinopathies. 13,14 In the second biopsy of this patient, we also see a large number of lymphocyte infiltrations around small blood vessel of the perimysium besides a severe variation of fiber size with a lot of degenerating, necrotic, and regenerating fibers. Patients with muscular dystrophy often have slight numbness, which can have spontaneous resolution.…”
Section: Discussionmentioning
confidence: 72%
“…Its increased expression is observed in patients with chronic inactive inflammatory myopathy as well as with active inflammatory myopathy. It is detectable even after the initiation of immunosuppressive treatment (17), Contrarily, MHC-Class I complex is not over-expressed in dysferlinopathies. Therefore, immunostained MHC class 1 complex is a valuable marker for differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…While it is widely accepted that MHC-class 1 expression is up-regulated in inflammatory myopathies, it is not clear whether it is a result ofthe nonspecific response to muscle degeneration or of the specific disease process itself (17), Previous reports have shown that MHC-class 1 is induced by several proinflammatory cytokines which are highly expressed in inflammatory myopathies. Normally MHC class 1 is not expressed on the sarkolemma of both normal and myopathie muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Prominent muscle pain and the presence of inflammatory infiltrates on muscle biopsy led to an initial misdiagnosis of polymyositis, which occurred in 25% of LGMD2B cases in one series 1. Several histological features differentiate the two forms of myopathy, including the location of the inflammatory lymphocytic infiltrate that involves both necrotic and non‐necrotic fibers in polymyositis compared with just necrotic fibers in LGMD2B 8. Consequently, it is essential that the pathologist, having received detailed clinical information from the treating physician, comments on the site of any inflammatory lymphocytic infiltrate to avoid the use of inappropriate immunomodulatory therapy in LGMD2B.…”
Section: Discussionmentioning
confidence: 99%